Transcriptomic Abnormalities in Epstein Barr Virus Associated T/NK Lymphoproliferative Disorders - de Mel, Sanjay; Tan, Joshua Zhi-Chien; Jeyasekharan, Anand D.; Chng, Wee-Joo; Ng, Siok-Bian (Frontiers in Pediatrics, 2019)
Epstein Barr virus positive T/NK lymphoproliferative disorders (EBV-TNKLPD) comprise a spectrum of neoplasms ranging from cutaneous lymphoid proliferations to aggressive lymphomas. The spectrum includes extranodal NK/T-cell lymphoma (ENKTL), aggressive NK-cell leukemia and a group of EBV-TNKLPDs affecting children which are poorly characterized in terms of their molecular biology. Gene and miRNA expression profiling has elucidated RNA abnormalities which impact on disease biology, classification and treatment of EBV-TNKLPD. Pathways promoting proliferation, such as Janus associated kinase/ Signal Transducer and Activator of Transcription (JAK/STAT) and nuclear factor kB are upregulated in ENKTL while downregulation of survivin and deregulation of p53 inhibit apoptosis in both ENKTL and chronic active EBV infection (CAEBV). Importantly, immune evasion via the programmed cell death-1 and its ligand, PD-1/PD-L1 checkpoint pathway, has been demonstrated to play an important role in ENKTL. Other pathogenic mechanisms involve EBV genes, microRNA deregulation, and a variety of other oncogenic signaling pathways. The identification of EBV-positive Peripheral T-cell lymphoma not otherwise specified (PTCL-NOS) as a tumor with distinct molecular signature and clinical characteristics highlights the important contribution from the knowledge derived from gene and miRNA expression profiling in disease classification. Novel therapeutic targets identified through the study of RNA abnormalities provide hope for patients with EBV- TNKLPD which often have a poor prognosis. Immune checkpoint inhibition and JAK inhibition in particular have shown promise and are being evaluated in clinical trials. In this review, we provide an overview of the key RNA aberrancies in EBV+ TNKLPD and discuss their translational potential.